2015
DOI: 10.1111/papr.12282
|View full text |Cite
|
Sign up to set email alerts
|

Low Pain Catastrophization and Disability Predict Successful Outcome to Radiofrequency Neurotomy in Individuals with Chronic Whiplash

Abstract: Low levels of pain catastrophizing and disability independently predicted a successful response to cRFN in patients with chronic WAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…These align with Severeijns et al [31], who mentioned that catastrophizing is significantly associated with the psychological and social aspects of quality of life in chronic pain patients. This study also supports several other studies which reported that catastrophizing has negative impacts for patients with chronic pain [121719202132].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These align with Severeijns et al [31], who mentioned that catastrophizing is significantly associated with the psychological and social aspects of quality of life in chronic pain patients. This study also supports several other studies which reported that catastrophizing has negative impacts for patients with chronic pain [121719202132].…”
Section: Discussionsupporting
confidence: 91%
“…Catastrophizing refers to an exaggerated negative interpretation to an expected or actual experience of pain, and is characterized by magnification of the potential negative aspects of pain, a feeling of helplessness in coping with pain, and an inability to disengage from thoughts about pain in anticipating, during, or after experiencing pain [17]. Catastrophizing is an important factor in determining how cognition, belief, coping strategy, and functioning relate to the pain experience [12], and correlates with pain intensity, disability, lowered pain threshold, a worse prognosis, and poorer responses to pain intervention [18192021]. Catastrophizing consists of 3 factors, which are (1) rumination, which refers to ruminative thoughts, worry, and an inability to inhibit pain-related thoughts; rumination reflects an inability to suppress or divert attention away from pain-related thoughts; (2) magnification, refers to a tendency to exaggerate the unpleasantness of pain and expectancies for negative outcomes; and (3) helplessness, reflecting the inability to deal with painful situations [22].…”
Section: Introductionmentioning
confidence: 99%
“…189,216,217 Similar findings are evident in studies of chronic LBP, as QST-assessed indices of pain sensitivity and pain modulation show significant prospective associations with pain intensity and disability following treatment. 182 Moreover, psychosocial factors such as depression, anxiety, distress, and catastrophizing seem to have fairly general effects, as these variables have been prospectively associated in recent studies with: greater physical disability and reduced treatment response among patients with RA treated with steroids, 168 patients with chronic back pain undergoing acupuncture, 28 patients with chronic neck pain treated with radiofrequency lesioning or facet blocks, 219,220 patients with chronic pelvic pain undergoing surgery, 131 patients with whiplash managed with multimodal rehabilitation, 51 primary care patients experiencing back pain, 173 patients with orofacial pain receiving injection therapies, 164 patients with FM enrolled in an exercise program, 43 patients with irritable bowel syndrome undergoing CBT, 30 patients with neck pain treated with manual therapy, 64 and many other combinations of nonneuropathic chronic pain with a variety of treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings are evident in studies of chronic LBP, as QST-assessed indices of pain sensitivity and pain modulation show significant prospective associations with pain intensity and disability following treatment [182]. Moreover, psychosocial factors such as depression, anxiety, distress, and catastrophizing appear to have fairly general effects, as these variables have been prospectively associated in recent studies with: greater physical disability and reduced treatment response among RA patients treated with steroids [168], chronic back pain patients undergoing acupuncture [28], chronic neck pain patients treated with radiofrequency lesioning or facet blocks [219;220], chronic pelvic pain patients undergoing surgery [131], whiplash patients managed with multimodal rehabilitation [51], primary care patients experiencing back pain [173], orofacial pain patents receiving injection therapies [164], Fibromyalgia patients enrolled in an exercise program [43], IBS patients undergoing CBT [30], neck pain patients treated with manual therapy [64], and many other combinations of non-neuropathic chronic pain with a variety of treatment approaches.…”
Section: Discussionmentioning
confidence: 99%